2014
DOI: 10.2903/j.efsa.2014.3665
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on the assessment of the toxigenic potential of Bacillus species used in animal nutrition

Abstract: Bacillus species are used in animal production directly as microbial feed additives or as the source of other feed additives, notably enzymes. The principal safety concern for consumers and, to a lesser extent livestock, associated with Bacillus is a capacity for toxin production. However, the capacity for toxin production and the nature of the toxins produced is unevenly distributed over the genus, occurring frequently in some species and more rarely in others. In principle, the selection of strains belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…EFSA considered these issues in its opinion on the safety and efficacy of Bacillus subtilis PB6 as a feed additive for chickens for fattening (EFSA FEEDAP Panel, 2009) following the provisions of the guidance applicable at the time and concluded that the strain could be presumed safe for the target species, consumers and the environment. Subsequently, EFSA has introduced new guidance on the determination of antibiotic susceptibility (EFSA FEEDAP Panel, 2012b) and assessing the toxigenic potential of Bacillus species (EFSA FEEDAP Panel, 2014). Consequently, these elements of the previous assessment are reconsidered in this opinion.…”
Section: Introductionmentioning
confidence: 99%
“…EFSA considered these issues in its opinion on the safety and efficacy of Bacillus subtilis PB6 as a feed additive for chickens for fattening (EFSA FEEDAP Panel, 2009) following the provisions of the guidance applicable at the time and concluded that the strain could be presumed safe for the target species, consumers and the environment. Subsequently, EFSA has introduced new guidance on the determination of antibiotic susceptibility (EFSA FEEDAP Panel, 2012b) and assessing the toxigenic potential of Bacillus species (EFSA FEEDAP Panel, 2014). Consequently, these elements of the previous assessment are reconsidered in this opinion.…”
Section: Introductionmentioning
confidence: 99%
“…EFSA considered these issues in its opinion on the safety and efficacy of Calsporin ® as a feed additive for weaned piglets (EFSA FEEDAP Panel, 2010a), following the provisions of the guidance applicable at the time, and concluded that the strain could be presumed safe for the target species, consumers and the environment. Subsequently, EFSA has introduced new guidance on the determination of antibiotic susceptibility (EFSA FEEDAP Panel, 2012) the toxigenic potential of Bacillus species (EFSA FEEDAP Panel, 2014). Consequently, these elements of the previous assessment are reconsidered in this opinion.…”
Section: Additional Informationmentioning
confidence: 99%
“…EFSA considered these issues in its opinion on the safety and efficacy of Bacillus subtilis PB6 as a feed additive for chickens for fattening (EFSA FEEDAP Panel, 2009) using the guidance applicable at the time and concluded that the strain could be presumed safe for the target species, consumers and the environment. Subsequently, EFSA introduced new guidance on the determination of antibiotic susceptibility (EFSA FEEDAP Panel, 2012b) and assessing the toxigenic potential of Bacillus species (EFSA FEEDAP Panel, 2014). These issues were reconsidered taking account of the latest guidance in the context of an Opinion on an extension of use for laying hens and minor laying poultry birds (EFSA FEEDAP Panel, 2015).…”
Section: Safetymentioning
confidence: 99%